Energy Management Strategies for Electric and Plug-in Hybrid Electric Vehicles - Williamson, Sheldon S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book addresses the practical issues for commercialization of current and future electric and plug-in hybrid electric vehicles (EVs/PHEVs). The volume focuses on power electronics and motor drives based solutions for both current as well as future EV/PHEV technologies. Propulsion system requirements and motor sizing for EVs is also discussed, along with practical system sizing examples. PHEV power system architectures are discussed in detail. Key EV battery technologies are explained as well as corresponding battery management issues are summarized. Advanced power electronic converter topologies for current and future charging infrastructures will also be discussed in detail. EV/PHEV interface with renewable energy is discussed in detail, with practical examples.
Introduction -- Electric and Plug-in Hybrid Electric Vehicle Drivetrain Topologies -- EV and PHEV Energy Storage Systems -- Hybrid Electric and Fuel Cell Hybrid Electric Vehicles -- EV and PHEV Battery Technologies -- On-Board Power Electronic Battery Management -- EV and PHEV Battery Charging: Grid and Renewable Energy Interface -- Power Electronic Converter Topologies for EV/PHEV Charging -- EVs and PHEVs for Smart Grid Applications -- EV and PHEV Well-to-Wheels (WTW) Efficiency Analysis.
Keywords: Chemistry; Production of electric energy or power; Energy; Transportation; Power Electronics, Electrical Machines and Networks; Electrochemistry